TRANSFORMATIVE LEADERSHIP IN ISLAMIC EDUCATION: A SYSTEMATIC REVIEW OF ITS IMPACT ON INSTITUTIONAL PERFORMANCE - Sugito Sugito (Penelitian dan Pengembangan Ilmu, 2025)
Transformative leadership in Islamic education plays a crucial role in improving institutional performance, especially in facing the challenges of globalization and social change. Although many studies have discussed transformative leadership in the context of general education, studies that specifically highlight its impact on Islamic educational institutions are still limited. This research aims to explore the relationship between transformative leadership practices and the performance of Islamic educational institutions, as well as identifying relevant indicators of success in this context. This research uses a Systematic Literature Review (SLR) approach by analyzing publications from leading academic databases such as Scopus and Web of Science. The data selection and analysis process was carried out using the PRISMA framework, as well as a thematic analysis approach to identify the main patterns and themes that emerged in the literature. Research findings show that transformative leadership which includes idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration has a significant influence on increasing organizational effectiveness, satisfaction of teaching staff, and innovation in educational policies in Islamic institutions. This research provides a theoretical contribution to the study of Islamic educational leadership and offers practical recommendations for institutional leaders to implement transformative leadership strategies to improve the quality of education and the effectiveness of institutional management.